(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article destroys the nourishment of the stylistic evolution of Western European culture, represented by architectural and musical mysteries. There is an idea about the continuation of material and spiritual ambushes in architecture and music. The author explores the underlying trends and eminence in these types of art, draws parallels with architectural disputes and musical creations in the singing era in different countries. The connections between religious ideas and the development of musical forms and genres and in cult disputes are explored. There are categories of style that are characteristic of rice in historical, national, cultural aspects. The study demonstrates the regularity of “nearby” stylistic trends and its brightest representatives. Also analyzed are the applications of stylistic retrospectives of later eras, much more than earlier ones, including ancient eras. The author draws an analogy between musical modes and orders in architecture; between the steps of harmony, as a musical concept, and the steps of the booths, as well as architectural categories and other elements of the human body. Respect is given to the importance of acoustic aspects, sound vibrations in architecture and music, as well as color schemes in booths and musical works, including “programmed” music and interior design. The evolution of various musical genres and the evolution of musical instruments are borne out. The aesthetic aspect of these musical instruments is seen as storage accessories. Parallels are drawn between the decor of architectural buildings and the ornamentation of music, in connection with the song’s stylistic direction. The moments of formation are considered - the main elements of successful architecture and music, the evolution of form in these types of mysticism. The evolution of styles in architecture and music can be seen in the historical trends that shape the stylistic advance.